Studies of the magnetoresistive peak due to interlayer coherence in a quasi-two-dimensional superconductor - Goddard, P; Singleton, J; Ardavan, A; Harrison, N; Blundell, S; Schlueter, J; Kini, A (2003)
Peaks in the interlayer magnetoresistance of the layered superconductor kappa-(BEDT-TTF)(2)Cu(NCS)(2) are observed in the presence of an exactly in-plane magnetic field. The existence of these resistance peaks implies the presence of a three-dimensional Fermi surface extending in the interlayer region. Analysis of the width of the peaks yields a value for the interlayer transfer integral. (C) 2002 Elsevier Science B.V. All rights reserved.